2018
DOI: 10.26858/talenta.v4i1.6842
|View full text |Cite
|
Sign up to set email alerts
|

Tantangan Pendidikan di Era Disruptif: Ujian Online Berbasis Smartphone dengan Pengembangan Aplikasi xSIA

Abstract: Xsia21.xSIA.app was a digital archive system that simplified the lecturer in conducting, verifying and analysing the test result. The paperless method aimed to facilitate the participants to perform an examination without paper and pencil and for the lecturer to check the result as well. The participants in this study were 35 students. Participants filled four kinds of online assessment are questionare of paperless method, questionare of interview subject scale, true false test and multiple choice test. Test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Disruptive, namely a condition description of the old patterns and systems with new, more innovative and creative ways (Bakar et al, 2018). The era of disruption is marked by rapid technological advances that can change social behaviour, especially among students.…”
Section: Deviant and Casual Behavior In A Disruptive Eramentioning
confidence: 99%
“…Disruptive, namely a condition description of the old patterns and systems with new, more innovative and creative ways (Bakar et al, 2018). The era of disruption is marked by rapid technological advances that can change social behaviour, especially among students.…”
Section: Deviant and Casual Behavior In A Disruptive Eramentioning
confidence: 99%
“…Namely, the application with hundreds of users has yet to be tested at once, and the user must have an internet connection when using the application from start to finish. Another study by Mas Bakar et al (2018) concluded that smartphone and computer-based exams facilitate the preparation and completion of activities ranging from administration to exam results. However, this study has several areas for improvement, namely the need for more security when using the application.…”
Section: Introductionmentioning
confidence: 99%